Refeeding Syndrome in a Critically Ill Child - Souza, Fabíola I. Suano de; Leite, Heitor Pons; Chwals, Walter Jacob; Carvalho, Werther Brunow de (International Journal of Child Health and Nutrition, 2014)
Objective: To report a case of a child interned in an ICU of a University Hospital who developed refeeding syndrome, and to review the specific literature pertinent to this area. Case Report: An eight year-old, previously healthy, male patient was admitted for necrotizing pneumonia. On admission the child had a z-score of weight for height of 0.38 and height for age of -0.74. Following 60 days’ hospital admission he had lost 27.5% of initial weight. Enteral tube feeding, with an energy intake equivalent to the basal metabolic rate plus 20% for stress, was initiated and gradually increased during the stabilization phase. After receiving 2000 kcal/day for 5 days, hypophosphatemia was detected in association with an increase in hepatic enzymes and hyperglycemia. No concomitant worsening of the white blood count or evidence of inflammatory activity was present. These alterations were accompanied by an increase in pulse rate and body temperature, thereby leading to a diagnosis of refeeding syndrome. Energy intake decreased to 1520 kcal/day, resulting in a marked improvement of the laboratorial parameters in less than a week. Conclusions: Refeeding syndrome is a potentially dangerous complication of increased caloric administration in critically ill pediatric patients. Early recognition and appropriate adjustment of nutritional support is important to avoid the serious consequences which may ensue if this condition is left untreated.